Computational Science and Technology 5th ICCST 2018, Kota Kinabalu, Malaysia, 29-30 August 2018 - Alfred, Rayner; Lim, Yuto; Ibrahim, Ag Asri Ag; Anthony, Patricia (Lecture Notes in Electrical Engineering,, 2019)
This book features the proceedings of the Fifth International Conference on Computational Science and Technology 2018 (ICCST2018), held in Kota Kinabalu, Malaysia, on 29-30 August 2018. Of interest to practitioners and researchers, it presents exciting advances in computational techniques and solutions in this area. It also identifies emerging issues to help shape future research directions and enable industrial users to apply cutting-edge, large-scale and high-performance computational methods.